COVID-19 Pandemic: Theory, Concepts and Challenges - Banerjee, Anindya; Ghosh, Raj krishan; Basak, Surajit; Dey, Arijit (Understanding COVID-19: The Role of Computational Intelligence, 2022)
Coronavirus is a single-stranded RNA virus, with a size of about 120 nm. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) is an infectious disease caused by a recently discovered coronavirus Disease 2019 (COVID-19) novel coronavirus and is a major global pandemic that has already taken more than 600 thousand lives. This disease is spreading rapidly across the globe and already has more than 14 million confirmed cases worldwide. It can be latent with low or no symptoms at all for initial days after transmission. The exponential increase in new cases each day calls for swift, responsive measures and rapid control at the individual, societal, and governmental levels. Lack of awareness about COVID-19 and negligence in implementation of protective measures poses a greater threat to human lives in this pandemic. There is a shortage in hospital wards as well as the absence of proper medicine for recovery. Necessary consumer products like masks and sanitizers are short in supply and unable to quench the demand. This chapter aims to present a clear and concise idea of the nature of COVID-19, its classification, and its characteristics. Classification refers to the hierarchical naming and the reason behind the protocol accepted. The characteristics refer to the nature of the virus, sources of spreading, its strengths and weaknesses, just to name a few. Causes and symptoms related to this disease are explained in detail. Modes of transmission and infection are discussed. The latest and the most accurate data and findings are listed and described. Common misconceptions and misinformation are examined, analyzed, and debunked. The after-effects and steps to take are reviewed. The preventive, as well as curative measures, are conferred. Current and future challenges are also enumerated and summarized.
CRIS-Team Scopus Importer:2021-08-13
Keywords: COVID-19; Curative measures; Detailed statistics; Mode of Transmission; Preventive measures